Volume 4: Pipelining in Northern and Offshore Environments; Strain-Based Design; Risk and Reliability; Standards and Regulation 2012
DOI: 10.1115/ipc2012-90247
|View full text |Cite
|
Sign up to set email alerts
|

An Update to the UKOPA Pipeline Damage Distributions

Abstract: The United Kingdom Onshore Pipeline Operators Association (UKOPA) was formed by UK pipeline operators to provide a common forum for representing operators interests in the safe management of pipelines. This includes providing historical failure statistics for use in pipeline quantitative risk assessment and UKOPA maintain a database to record this data. The UKOPA database holds data on product loss failures of UK major accident hazard pipelines from 1962 onwards and currently has a total length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…During 30 years of operation, hydrocarbon gas buried onshore pipelines in Indonesia experienced 18 leaks and ruptures or 5.32E‐04/km‐year on average. Compared with the latest edition of EGIG, UKOPA, PNGPC, and PHMSA pipeline failure rates of 2.90E‐04/km‐year, 9 2.12E‐04/km‐year, 10 1.81E‐04/km‐year, 17 and 1.40E‐04/km‐year, 11 respectively. Indonesia's failure rate is significantly higher.…”
Section: Frequency Of Failuresmentioning
confidence: 99%
See 3 more Smart Citations
“…During 30 years of operation, hydrocarbon gas buried onshore pipelines in Indonesia experienced 18 leaks and ruptures or 5.32E‐04/km‐year on average. Compared with the latest edition of EGIG, UKOPA, PNGPC, and PHMSA pipeline failure rates of 2.90E‐04/km‐year, 9 2.12E‐04/km‐year, 10 1.81E‐04/km‐year, 17 and 1.40E‐04/km‐year, 11 respectively. Indonesia's failure rate is significantly higher.…”
Section: Frequency Of Failuresmentioning
confidence: 99%
“…19 Another source 20 suggested the NEB causal model such as defect and deterioration, corrosion and cracking, equipment failure, incorrect operation, external interference, and natural force damage. This study followed the causal group suggested by UKOPA: Girth weld defect, external interference, internal corrosion, external corrosion, pipe material defect, ground movement, and seam weld defect 10 (Figure 4). such as UKOPA, PNGPC, and Alberta, where ground movement accounts for a small proportion of failures (3.5%, 4%, and 3.33%, respectively).…”
Section: Causal Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Similar issues are prevalent in gas and oil pipelines as well as water pipelines. The European Gas Pipeline Incident Data Group 10 and the United Kingdom Onshore Pipeline Operators' Association 11 reported that approximately 28.3% (2007-2016) and 21.6% (1962-2019) of pipeline failures were induced by TPI. Therefore, the structural health monitoring (SHM) technology has emerged to prevent their failures of buried pipelines and solve the social issues related to them.…”
Section: Introductionmentioning
confidence: 99%